Ujian Nasional sebagai Panoptikon Bangsa - Gianto, Gianto (Program Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2014)
National Examination is the assessment of learning outcomes by the government which aims to assess the achievement of national competency on specific subjects in the group of subjects in science and technology. The results are used as one of the considerations for mapping the program quality or the educational unit, as the basic selection to the next education level, determining students' graduation, and giving scholarship for improving the quality of education. Panopticon was originally a concept of the prison building designed by English philosopher and social theorist Jeremy Bentham in 1785. The design concept was allowing a guard to watchÂ prisoners everywhere. Later, Panopticon not merely architectural designs, but he became a model of community supervision and discipline, which also applied today. National Exam as State Panoptikon is a philosophical concept where the values in National Examination is examined or analyzed using the concepts and values of Panoptikon